1999
DOI: 10.1021/ja991729e
|View full text |Cite
|
Sign up to set email alerts
|

On the Meaning of Affinity:  Cluster Glycoside Effects and Concanavalin A

Abstract: The inhibition of protein−carbohydrate interaction provides a powerful therapeutic strategy for the treatment of myriad human diseases. To date, application of such approaches have been frustrated by the inherent low affinity of carbohydrate ligands for their protein receptors. Because lectins typically exist in multimeric assemblies, a variety of polyvalent saccharide ligands have been prepared in the search for high affinity. The cluster glycoside effect, or the observation of high affinity derived from mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
185
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(198 citation statements)
references
References 67 publications
8
185
2
Order By: Relevance
“…The diminution of −DH was therefore considered the thermodynamic signature for the intermolecular aggregation process. 91, 97 Studies previously carried out by Toone and co-workers employing another series of dendritic multivalent ligands, 96 where crystals of both bi-and trivalent ligands were grown in the presence of succinylated Con A, showed that the carbohydrate orientation within the binding site was identical to that of the corresponding monovalent ligand. Interestingly, ligands with valencies greater than three showed affinity enhancements in agglutination assay but not by ITC.…”
Section: Multivalent Ligandsmentioning
confidence: 95%
“…The diminution of −DH was therefore considered the thermodynamic signature for the intermolecular aggregation process. 91, 97 Studies previously carried out by Toone and co-workers employing another series of dendritic multivalent ligands, 96 where crystals of both bi-and trivalent ligands were grown in the presence of succinylated Con A, showed that the carbohydrate orientation within the binding site was identical to that of the corresponding monovalent ligand. Interestingly, ligands with valencies greater than three showed affinity enhancements in agglutination assay but not by ITC.…”
Section: Multivalent Ligandsmentioning
confidence: 95%
“…The formyl substituents were reduced with NaBH 4 [25] and the primary alcohols were selectively converted into chlorides with SOCl 2 . [26] Final substitution with Dpa was performed as described above.…”
Section: Synthesismentioning
confidence: 99%
“…In this respect, it was possible to control the hydrophilic/hydrophobic ratio of the copolymer by increasing the amount of sugar moieties or by attaching long aliphatic chains as well as to generate a pH-sensitive system using 3-mercaptopropionic acid as thiol component (Scheme 3). The reaction was performed according to the method reported by Hawker et al 39 The thiols were added in slight excess (2 equiv of Ac 4 GlcSH with respect to the amount of double bonds) up to a large excess (10 equiv of 3-mercaptopropionic acid as well as dodecanethiol with respect to the number of double bonds) to the polymer solution. A radical photoinitiator (DMPA) was employed to accelerate the reaction.…”
Section: Thiolàene Photoaddition and Deacetylation Reactionsmentioning
confidence: 99%
“…The rate constant of EtOx at 100°C was determined to be 6.5 Â 10 À3 L 3 mol À1 3 s À1 , which is one order of magnitude slower than a polymerization at 140°C in the microwave. The disappearance of the monomer signal in the SEC, as depicted in Figure 2 (left), allowed a rough estimation of the required time for a full conversion of Ac 4 GlcYnOx. The exact calculation of the polymerization rate was not possible with the common methods because Ac 4 GlcYnOx could not be detected in GC.…”
mentioning
confidence: 99%
See 1 more Smart Citation